1957
DOI: 10.1021/ac60125a002
|View full text |Cite
|
Sign up to set email alerts
|

Study of Accuracy in Chemical Analysis Using Linear Calibration Curves

Abstract: It can be more easily detected in quantitative fashion by observing the 511-k.e.v. annihilation quanta produced when the positron and a free electron mutually annihilate. To simplify the determination of the counting geometry, it is necessary to ensure that all positrons are stopped in the immediate vicinity of the source.Niteogen -14(d, «)Oxygen-15. The nuclide oxygen-15 has an inconveniently short life of 2.1 minutes. In order to get a reproducible counting rate of oxygen-15 from a given nitrogen sample, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

1961
1961
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(70 citation statements)
references
References 16 publications
2
68
0
Order By: Relevance
“…5) at the 95% confidence level following the method of Mandel and Linnig. 22 It is evident from the figure that the point for which the intercept is zero fell well within the ellipse, thus confirming no significant difference from zero. The validity of the proposed methods was tested by adding a fixed amount of pure drug to preanalyzed dosage forms.…”
Section: Fixed-time Methodsmentioning
confidence: 56%
“…5) at the 95% confidence level following the method of Mandel and Linnig. 22 It is evident from the figure that the point for which the intercept is zero fell well within the ellipse, thus confirming no significant difference from zero. The validity of the proposed methods was tested by adding a fixed amount of pure drug to preanalyzed dosage forms.…”
Section: Fixed-time Methodsmentioning
confidence: 56%
“…20) Because the point (0, 1) lay inside the EJCR (at a confidence level of pϭ0.05) as shown in Fig. 7, it could be concluded that proportional and constant biases were absent, and thus the final calibration model showed good linearity.…”
Section: Resultsmentioning
confidence: 89%
“…The value of t-were found to be 1.81 and 1.78 for Ideally the true relation between found and added concentration will provide straight line passing through the origin (intercept 0) with a slope equal to unity [31].…”
Section: Optimization Of Variablesmentioning
confidence: 94%